1, 3, 2‐Diazaphospholene‐Catalyzed Reductive Cyclizations of Organohalides. (6th May 2022) - Klett, Johannes; Woźniak, Łukasz; Cramer, Nicolai
Abstract: 1, 3, 2‐diazaphospholenes hydrides (DAP‐Hs) are highly nucleophilic organic hydrides serving as main‐group catalysts for a range of attractive transformations. DAP hydrides can act as stoichiometric hydrogen atom transfer agents in radical reactions. Herein, we report a DAP‐catalyzed reductive radical cyclization of a broad range of aryl and alkyl halides under mild conditions. The pivotal DAP catalyst turnover was achieved by a DBU‐assisted σ ‐bond metathesis between the formed DAP halide and HBpin, which rapidly regenerates DAP‐H. The transformation is significantly accelerated by irradiation with visible light. Mechanistic investigations indicate that visible light irradiation leads to the formation of DAP dimers, which are in equilibrium with DAP radicals and accelerate the cyclization. The direct use of (DAP)2 enabled a catalytic protocol in the absence of light. Abstract : 1, 3, 2‐diazaphospholenes hydrides (DAP‐H) are shown as efficient catalysts for reductive radical cyclization of aryl and alkyl halides under irradiation with visible light. The pivotal DAP catalyst turnover was achieved by a DBU‐assisted σ ‐bond metathesis between the formed DAP halide and HBpin.